Economic valuation of water supply service from two community forests in Palpa district - Khanal, Y; Upadhyaya, CP; Sharma, RP (Banko Janakari, 2010)
Apart from physical products, community forests (CF) in Nepal generate various ecosystem services that could be important not only to the stakeholders at local level, but also to the stakeholders at the regional and the global levels. Water supply from CF would be one of the many ecosystem services whose benefits are provided to the stakeholders. Considering the economic importance of water supply service from CF, this study aims to assess the economic value of the water supply as a service from two CFs and also identify the factors affecting an individual's willingness to pay (WTP). Contingent valuation method was applied to evaluate the water supply service based on the information of users' WTP. Data from 74 households (HH) in Lipindevi Thulopakho and Jarneldhara CFs in Palpa district (surveyed during May-June, 2008) were used. Results indicated that the mean WTP of Lipindevi Thulopakho and Jarneldhara CF users were US 36.62 and 25.62 HH-1 yr-1, respectively. The economic value of water supply service from Lipindevi Thulopakho and Jarneldhara CF were US 93.54 ha-1 yr-1 and 134.06 ha-1 yr-1, respectively. Factors like distance of the house from water source, daily water consumption, wealth status and caste were associated with substantial influences on an individual's WTP. This study concludes that there would be a high possibility for generating extra income with the development of a payment mechanism for water supply service from CF. Key words: Community forest; contingent valuation; economic valuation; water supply; willingness to pay DOI: 10.3126/banko.v20i1.3505 Banko Janakari, Vol. 20, No. 1 pp.24-29